Digitization of Aging-in-Place: An International Comparison of the Value-Framing of New Technologies - Barbara L. Marshall; Nicole K. Dalmer; Stephen Katz; Eugene Loos; Daniel López Gómez; Alexander Peine (Societies, 2022)
Planning for aging populations has been a growing concern for policy makers across the globe. Integral to strategies for promoting healthy aging are initiatives for ‘aging in place’, linked to services and care that allow older people to remain in their homes and communities. Technological innovations—and especially the development of digital technologies—are increasingly presented as potentially important in helping to support these initiatives. In this study, we employed qualitative document analysis to examine and compare the discursive framing of technology in aging-in-place policy documents collected in three countries: The Netherlands, Spain, and Canada. We focus on the framing of technological interventions in relation to values such as quality of life, autonomy/independence, risk management, social inclusion, ‘active aging’, sustainability/efficiency of health care delivery, support for caregivers, and older peoples’ rights. The findings suggest that although all three countries reflected common understandings of the challenges of aging populations, the desirability of supporting aging in place, and the appropriateness of digital technologies in supporting the latter, different value-framings were apparent. We argue that attention to making these values explicit is important to understanding the role of social policies in imagining aging futures and the presumed role of technological innovation in their enactment.